Oxidative Stress and Carcinogenesis: Potential of Phytochemicals in Breast Cancer Therapy. (3rd April 2017) - Forcados, Gilead Ebiegberi; James, Dorcas Bolanle; Sallau, Abdullahi Balarabe; Muhammad, Aliyu; Mabeta, Peace
ABSTRACT: Breast cancer remains a burden in both developed and developing countries, with higher mortality in developing countries. Attempts to eradicate cancer have not been successful despite the progress made in the development of more novel chemotherapeutic drugs. Reactive-oxygen-species-mediated oxidative stress is known to play a role in breast cancer pathogenesis via genetic and epigenetic modifications, resulting in uncontrolled cell proliferation. Phytochemicals could provide leads for the development of alternative therapeutic agents due to their antioxidant activity, as well as their ability to induce apoptosis in cancer cells. However, most of the studies carried out using in vitro models do not continue with further studies in estrogen-receptor-positive in vivo breast cancer models, or fail to examine the possible biochemical mechanisms of phytochemical-based amelioration. This review examines oxidative-stress-mediated carcinogenesis and the potential of phytochemicals as anticancer agents.